The Role of Teacher Creativity in Improving Motivation and Learning Achievement of Seventh-Grade Students at Madrasah Tsanawiyah - Muhamad Alwi Al Maliki; Muchamad Suradji (Universitas Islam Negeri Sumatera Utara, 2025)
Teacher creativity is a crucial element in creating meaningful, enjoyable, and effective learning processes that contribute to improved student academic performance. Creative teachers are able to design varied and innovative learning strategies that align with students' individual characteristics. This study aims to describe the role of teacher creativity in enhancing the academic achievement of Grade VII students at MTs Darul Ulum Medali, Sugio District, Lamongan Regency. A descriptive qualitative approach was employed, using data collection techniques such as observation, in-depth interviews, and documentation. The research informants consisted of subject teachers and Grade VII students. The findings reveal that teacher creativity is reflected in six main aspects: the use of engaging instructional media, implementation of varied teaching methods, communicative and enjoyable classroom management, contextual and challenging assignments, innovative assessment strategies, and positive student responses to learning activities. These six elements demonstrate that teacher creativity significantly enhances student motivation, active participation, and academic performance. Therefore, teacher creativity should not be seen as a complement but as a foundational factor in establishing effective and meaningful education, particularly in junior secondary school settings.